2021
DOI: 10.1080/13511610.2021.1879631
|View full text |Cite
|
Sign up to set email alerts
|

The role of proximity in stakeholder networks for Smart Specialisation: a Sparsely Populated Area case study

Abstract: The European Smart Specialisation Strategy (S3) with its underlying aim to support regional growth, cohesion, and innovation has by now been widely applied to European Sparsely Populated Areas (SPAs). Previous works have identified that intra-regional stakeholder networks are important for a successful S3 implementation, and that their establishment is related to the level of proximity between stakeholders; however, the nature of such networks in the context of developing S3 in SPAs deserves further investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…De Noni et al [2021] revealed that extending the knowledge complexity of regional portfolio can positively balance the negative effect of technological relatedness in the long-run. Additionally, the results of the study Ghinoi et al [2021] suggest that different dimensions of proximity, like geographical and cognitive proximity, are positively associated with intra-regional networks aimed at implementing S3.…”
Section: Theoretical Backgroundmentioning
confidence: 85%
“…De Noni et al [2021] revealed that extending the knowledge complexity of regional portfolio can positively balance the negative effect of technological relatedness in the long-run. Additionally, the results of the study Ghinoi et al [2021] suggest that different dimensions of proximity, like geographical and cognitive proximity, are positively associated with intra-regional networks aimed at implementing S3.…”
Section: Theoretical Backgroundmentioning
confidence: 85%
“…Geographical proximity enables stakeholders to interact more effectively which facilitates flows of knowledge, thus creating a better understanding of collaboration goals and building trust [ 59 ]. The positive effect of geographical proximity on stakeholder collaboration has been demonstrated in the context of regions where organisations and residents are located close to one another [ 60 , 61 ].…”
Section: Literature Reviewmentioning
confidence: 99%